The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0103-50532008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing codon usage bias in genomes

Abstract: O código genético é degenerado, isto é, o mesmo amino ácido pode ser codificado por vários codons. Apesar de codificarem o mesmo amino ácido, estes codons sinônimos não são utilizados da mesma forma em genomas diferentes, e mesmo em um único genoma o padrão de uso dos codons sinônimos pode variar muito entre os genes, ou ainda ao longo de um único gene. Com a recente introdução de seqüências genômicas completas as razões destes desvios no uso de codons estão começando a ser entendidas. Neste artigo nós vamos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Thus, codons that have the potential to form OSCs tend to be AT-rich and consequently are disproportionately prevalent in organisms with AT-rich genomes. Given that other selective forces or mutational biases determine the GC content of an organism [8,10-12], this implies that the relationship found between a codon’s usage and its propensity to form OSCs is a poor test of the predictions of the Ambush Hypothesis, as it is easily explained by the high AT content of stop codons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, codons that have the potential to form OSCs tend to be AT-rich and consequently are disproportionately prevalent in organisms with AT-rich genomes. Given that other selective forces or mutational biases determine the GC content of an organism [8,10-12], this implies that the relationship found between a codon’s usage and its propensity to form OSCs is a poor test of the predictions of the Ambush Hypothesis, as it is easily explained by the high AT content of stop codons.…”
Section: Resultsmentioning
confidence: 99%
“…Codon usage bias is known to vary between organisms and several hypotheses have been proposed to explain these differences [8]. The selection for OSCs predicted by the Ambush Hypothesis should be a very weak selective force as translational frameshifts affect a single protein product at a time, and regardless of the hypothesis, some level of OSCs is expected by chance.…”
Section: Introductionmentioning
confidence: 99%
“…The synonymous codons are not used at equal frequencies in coding sequences in many organisms [1]. This phenomenon called 'synonymous codon usage bias (SCUB)' reflects non-uniform usage of synonymous codons encoding the same amino acid during the translation of genes to proteins [2,3].The degree of SCUB divergence varies greatly among different species and genes [4][5][6][7]. SCUB was affected by many factors, including directional mutation, neutral selection [8], GC content, synonymous substitution rate [9], tRNA abundance [10], selection for efficient translation initiation [11], codon hydropathy and DNA replication initiation site [12], gene length [13] and expression level [14], etc.…”
mentioning
confidence: 99%
“…The degree of SCUB divergence varies greatly among different species and genes [4][5][6][7]. SCUB was affected by many factors, including directional mutation, neutral selection [8], GC content, synonymous substitution rate [9], tRNA abundance [10], selection for efficient translation initiation [11], codon hydropathy and DNA replication initiation site [12], gene length [13] and expression level [14], etc.…”
mentioning
confidence: 99%
“…Codon usage can differ widely not only between organisms, but also within a genome and within a single gene [16,25]. A lot of factors might cause different codon usage bias and the selective forces influencing it, such as selection for optimized translation, expression, location within genes, rate of evolution, secondary structure, nucleotide composition, protein length and environment [30]. It was demonstrated that many bacteria and yeast undergo translational selection, with highly expressed genes preferentially using codons assumed to be translated faster and/or more accurately by the ribosome [11,2].…”
Section: Introductionmentioning
confidence: 99%